2023
DOI: 10.1111/eci.14056
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for the causal linkage between telomere length and aortic aneurysm risk: A Mendelian randomisation study

Abstract: BackgroundEvidence of a clear causal relationship between telomere length and aortic aneurysms is limited by the potential for confounding or reverse causation effects. In this study, we used a Mendelian randomisation (MR) approach to investigate this putative causal association.MethodsIn total, 118 telomere length‐associated single‐nucleotide polymorphisms, identified in 472,174 individuals of European ancestry, were used as the instrumental variables. Summary statistics for genome‐wide association studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The occurrence of aneurysms in the anterior circulation arteries after the bifurcation of the internal carotid artery, as well as ascending aortic aneurysms, may be influenced to a greater extent by genetic factors. The MR study conducted by Zhang et al ( 4 ) provides additional evidence in support of a causal association between telomere length and arterial aneurysms. Specifically, the study found that individuals with longer telomere length had a decreased chance of developing arterial aneurysms.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The occurrence of aneurysms in the anterior circulation arteries after the bifurcation of the internal carotid artery, as well as ascending aortic aneurysms, may be influenced to a greater extent by genetic factors. The MR study conducted by Zhang et al ( 4 ) provides additional evidence in support of a causal association between telomere length and arterial aneurysms. Specifically, the study found that individuals with longer telomere length had a decreased chance of developing arterial aneurysms.…”
Section: Discussionmentioning
confidence: 90%
“…There may be shared genetic and pathological factors between them ( 3 ). Recent research findings suggest a potential causal association between the length of telomeres and the occurrence of aortic aneurysms ( 4 ). These findings offer promising prospects for the development of tailored treatment strategies.…”
Section: Introductionmentioning
confidence: 99%